Like, it's important: The frequency and use of the discourse marker like in older autistic children. (September 2022) - Jones, Rebekah; Zane, Emily R; Grossman, Ruth B
Background & Aims: Discourse markers, such as well or like, serve a variety of functions to support conversational reciprocity: filling pauses, aiding word-finding, and modulating turn-taking by holding the conversational floor. Previous research shows that autistic individuals use discourse markers less frequently than non-autistic (NonAu) peers; however, the discourse marker like has not been included in that research, despite its ubiquitous use by NonAu individuals, and despite the fact that like serves important pragmatic functions that are not encoded by any other discourse marker. Specifically, like signals to the listener that the content of upcoming speech is 1) Important/new; 2) Loose/approximate; 3) Reformulative; or 4) Quotative. The current study addresses this gap in the literature by comparing the frequency of discourse marker like use between older autistic and non-autistic children as well as exploring patterns of usage between the four like functions. Methods: Twenty-one 10-to-17-year-old children on the autism spectrum and 20 NonAu peers—statistically matched on age, sex, IQ and language scores—engaged in a semi-structured interview with a researcher. Uses of discourse-marker like were identified from written transcripts of interviews and each use was categorized into one of the four functions. Results: There were no significant differences in like frequencies between groups, nor were there differences in relative proportions of functions used by each group. Conclusions: Research consistently indicates that autistic individuals use discourse markers significantly less often than their NonAu counterparts, but the findings from our study suggest that this pattern does not persist to all such markers. This group of older autistic children use like as often as their peers and use it to signify similar information about upcoming speech to their listener.